Preventive Effects of Alpha-Lipoic Acid on Lipopolysaccharide-Induced Endothelial Dysfunction in Rats - Christianty, Fransiska Maria; Suharjono,; Susilo, Imam; Khotib, Junaidi (Pharmaceutical Sciences and Research, 2019)
Endothelial dysfunction has been considered as one of the key initial events in the pathogenesis of atherosclerosis and other cardiovascular diseases (CVDs). Several studies imply that chronic inflammation and oxidative stress play a critical role in endothelial dysfunction. The present study was designed to evaluate the preventive effect of alpha-lipoic acid (ALA) on lipopolysaccharide (LPS) induced endothelial dysfunction in rat based on malondialdehyde (MDA) level and vascular cell adhesion molecules-1 (VCAM-1) expression. Thirty Wistar rats were administered ALA for 2 weeks in different doses (30, 60, 120 mg.kg-1 BW) 1 hour before LPS 0.5 mg.kg-1 BW i.p challenge. The LPS was injected on 1st, 4th, and 9th day. MDA plasma level was analyzed with spectrophotometer λ 529 nm, and VCAM-1 expression was determined by immunohistochemistry. Pretreatment with ALA for 14 days could decrease plasma MDA level on LPS-induced endothelial dysfunction in rats. However, only one group of ALA doses, 120 mg.kg-1 BW, showed significant difference with LPS untreated group statistically. It was also found that ALA, in all treatment groups, could attenuate VCAM-1 expression. These findings suggest that ALA had a protective effect against endothelial dysfunction and may potentially prevent vascular inflammatory disease.